CPEC Development and Business Improvement: Analyzing the Mediating role of Quality of Life and Employment Opportunities - Nazirullah (Journal of Peace, Development and Communication, 2021)
China Pakistan Economic Corridor (CPEC) is a potential game-changer and a gigantic project for Pakistan. It brings massive development in the health sector, education sector, industry, businesses, trade, and infrastructure. The core objective of the research paper is to analyze the extent of influence of the CPEC for improvement of quality of life of the citizens, increasing business and employment opportunities. So, it is hypothesized that development of CPEC leads to better quality of life, creating employment opportunities, and improve businesses. Methodologically, an interview guide and survey were designed to gather primary data from the respondents. Respondents were purposively selected for in-depth assessment and asked to fill a questionnaire. Then, Responses were analyzed using thematic codes and structural equation modeling. The results proved that CPEC is a crucial factor in bringing changes in the quality of life, employment opportunities and business improvement in the Pakistan. On the basis of the results, it is recommended that the slow progress of the development of CPEC projects should be speed up immediately. The local businesses and industries should provide incentive to invest in the CPEC projects, and political consensus should be developed for effective implementation of the CPEC. Keywords: CPEC development, Employment Opportunities, Quality of Life, Business Improvement, SEM.